2021
DOI: 10.1111/tbed.14340
|View full text |Cite
|
Sign up to set email alerts
|

Natural co‐infection of divergent hepatitis B and C virus homologues in carnivores

Abstract: In humans, co‐infection of hepatitis B and C viruses (HBV, HCV) is common and aggravates disease outcome. Infection‐mediated disease aggravation is poorly understood, partly due to lack of suitable animal models. Carnivores are understudied for hepatitis virus homologues. We investigated Mexican carnivores (ringtails, Bassariscus astutus) for HBV and HCV homologues. Three out of eight animals were infected with a divergent HBV termed ringtail HBV (RtHBV) at high viral loads of 5 × 109 –1.4 × 1010 copies/ml ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Similarly, ancestral state reconstructions have previously shown that cross-species transmission from rodents is likely the source of the sloth and ringtail hepaciviruses ( Moreira-Soto et al. 2020 ; Jo et al. 2022 ).…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, ancestral state reconstructions have previously shown that cross-species transmission from rodents is likely the source of the sloth and ringtail hepaciviruses ( Moreira-Soto et al. 2020 ; Jo et al. 2022 ).…”
Section: Discussionmentioning
confidence: 85%
“…The clear relatedness between GmebHV and rodent hepacivirus (QLM02863), combined with evidence from our co-evolutionary analyses, suggests that this sequence might represent a cross-species transmission event between bats and rodents. Similarly, ancestral state reconstructions have previously shown that cross-species transmission from rodents is likely the source of the sloth and ringtail hepaciviruses (Jo et al 2022;Moreira-Soto et al 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Next-generation sequencing (NGS) analyses can be utilized to discover viral sequences in hosts, especially in cases of novel viruses with no reference sequences. With advances in NGS technology in recent years, new hepadnaviruses have been successively discovered in numerous animal species (metagenomic HBV), such as fish [4,7,8], frogs [6,9,10], bats [5,11], cats [12], dogs [13], antelope [14], raccoons [15], horses [16], and shrews [17][18][19]. These findings have yielded a deeper understanding of the origin and evolution of hepadnaviruses [20] together with studies on ancient HBV [21,22] and endogenous HBV in birds [23,24].…”
Section: Introductionmentioning
confidence: 99%